Pre-Viva Assessment System Development for FSKTM, UTHM - Chong, Zi Yong; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
The FSKTM pre-viva assessment system is an assessment information system designed for postgraduate students to submit a thesis draft for assessment before proceeding with the actual viva presentation. The current pre-viva assessment system is implemented in a hybrid manual system. Assessment forms are submitted via printed forms by students, while assessments by supervisors and panels are done by entering marks using the Google Forms function. While the process of calculating the overall score to produce evaluation results is also done manually (hand count) which leads to the risk of calculation errors. Thus, this web-based pre-viva assessment system has been developed to improve the existing process especially the application process, evaluation, and calculation of marks. The system also simplifies the process of data entry, information retrieval and management, as well as better analysis. System development follows the prototype model. The users of the system consist of administrator, supervisors, examiners, and students. The system implementation uses MySQL software via XAMPP, PHP, and Visual Studio Code. The developed system will be fully functional at the end of the project and provide faculty (FSKTM) with a web-based online platform to improve management quality from manual methods to centralized electronic methods that support pre-viva process efficiency.